2022
DOI: 10.1186/s40337-022-00661-3
|View full text |Cite
|
Sign up to set email alerts
|

Family, friends, and feelings: the role of relationships to parents and peers and alexithymia in adolescents with anorexia nervosa

Abstract: Background Anorexia nervosa (AN) is associated with impairments in socio-emotional functioning, including difficulties in interpersonal relationships as well as alexithymia (difficulties identifying and describing one’s emotions). Although the onset of the disorder is mostly in adolescence, a developmental period in which interpersonal relationships to parents as well as peers undergo major changes, only few studies have investigated the quality of interpersonal relationships in adolescent AN p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 80 publications
1
3
0
2
Order By: Relevance
“…The interview was administered to the adolescent participants by trained interviewers, i.e., study staff with a Bachelor's or Master's degree in Psychology who received several hours of training and supervision before conducting and evaluating the interviews. In previous studies using this training procedure we found the interrater-reliability of the Kinder-DIPS to be very good (e.g., accordance rates of 100% for current diagnoses of AN or MD in clinical groups as well as for no lifetime diagnoses in non-clinical groups; Lukas et al, 2022;Sfärlea et al, 2020), in line with Neuschwander et al (2013), who reported accordance rates of at least 97% for all diagnoses. However, interrater-reliability could not be assessed for the present study.…”
Section: Participantssupporting
confidence: 64%
“…The interview was administered to the adolescent participants by trained interviewers, i.e., study staff with a Bachelor's or Master's degree in Psychology who received several hours of training and supervision before conducting and evaluating the interviews. In previous studies using this training procedure we found the interrater-reliability of the Kinder-DIPS to be very good (e.g., accordance rates of 100% for current diagnoses of AN or MD in clinical groups as well as for no lifetime diagnoses in non-clinical groups; Lukas et al, 2022;Sfärlea et al, 2020), in line with Neuschwander et al (2013), who reported accordance rates of at least 97% for all diagnoses. However, interrater-reliability could not be assessed for the present study.…”
Section: Participantssupporting
confidence: 64%
“…In a large meta‐analysis by Murphy and Hutton (2018), the authors demonstrated that the alliance‐outcome relationship, for example, the correlation between therapeutic alliance and treatment success, is greater in 12‐ to 19‐year‐old individuals than in adults. Moreover, in a recent study, adolescents with AN reported a lower relationship quality with both their parents and peers than did healthy controls (Lukas et al., 2022). In contrast to their peer group in Germany, with approximately one‐half of people living in a relationship, only slightly more than one‐third of our sample had a partner.…”
Section: Discussionmentioning
confidence: 97%
“…Anorexia nervosa ist mit Schwierigkeiten, die eigenen Gefühle zu erkennen und zu verbalisieren (Alexithymie), sowie mit Schwierigkeiten in zwischenmenschlichen Beziehungen verbunden (Lukas et al. 2022 ).…”
Section: Hintergrund Und Fragestellungunclassified
“…Es kommt zum Verlust eines ganzheitlichen Körperselbsterlebens in verschiedene Geraden von Fragmentierung. Anorexia nervosa ist mit Schwierigkeiten, die eigenen Gefühle zu erkennen und zu verbalisieren (Alexithymie), sowie mit Schwierigkeiten in zwischenmenschlichen Beziehungen verbunden (Lukas et al 2022).…”
Section: Hintergrund Und Fragestellungunclassified